Auto-programmed heteroarchitecturing: Self-assembling ordered mesoporous carbon between two-dimensional Ti3C2Tx MXene layers. (November 2019) - Allah, Abeer Enaiet; Wang, Jie; Kaneti, Yusuf Valentino; Li, Tao; Farghali, Ahmed A.; Khedr, Mohamed Hamdy; Nanjundan, Ashok Kumar; Ding, Bing; Dou, Hui; Zhang, Xiaogang; Yoshio, Bando; Yamauchi, Yusuke
Abstract: Two-dimensional (2D) materials have attracted significant research interests for energy-storage applications owing to their unique structural and electronic properties. The modification of 2D materials with ordered mesoporous carbon (OMC) offers great opportunities for increasing the ion-accessible surface area and improving the ion diffusion. Herein, we report an unprecedented type of heterostructured MXene (Ti3 C2 Tx )/nitrogen-doped OMC (NOMC) hybrid, which is prepared via the self-assembly of melamine resol-P123 micelles with exfoliated Ti3 C2 Tx nanosheets. The NOMC exhibits well-ordered mesopores which are aligned with Ti3 C2 Tx nanosheet surface. This novel structure not only prevents the stacking of MXene nanosheets, but also provides a fast ion-diffusion path. When used as an electrode material for supercapacitors, the Ti3 C2 Tx -NOMC hybrid exhibits a high gravimetric capacitance of 329 F g −1 and a volumetric capacitance of 823 F cm −3 . Furthermore, the Ti3 C2 Tx -NOMC composite also displays excellent rate capability and good cycling stability, thus highlighting the benefit of hybridizing MXene with ordered mesoporous carbon for for enhancing the energy storage performance. Graphical abstract: An unprecedented type of heterostructured MXene (Ti3 C2 Tx )/nitrogen-doped OMC (NOMC) hybrid material is prepared via the self-assembly of phenol-melamine-formaldehyde resol-P123 micelles with exfoliated Ti3 C2 Tx nanosheets followed by carbonization.Image 1 Highlights: Heterostructured Ti3 C2 Tx /N-doped OMC (NOMC) hybrid is prepared via self-assembly of resol-P123 micelles with exfoliated Ti3 C2 Tx nanosheets. The NOMC layers can not only prevent the restacking of Ti3 C2 Tx layers, but also provide fast ion-diffusion paths. The Ti3 C2 Tx -NOMC hybrid exhibits both high gravimetric and volumetric performance as electrode material for supercapacitors.